Memories of former World War Two forced labourers - an international comparison - Thonfeld, Christoph (Oral History, 2011)
As most European societies have struggled to find a consensus for working up their World War Two past, former forced labourers often had to endure ensuing societal initiatives to suppress or instrumentalise their memories or to see them tied to overreaching political or ethical imperatives. This article tries to trace the whereabouts of these memories in societal and individual perspectives. First, forced labour in Nazi Germany can be seen as part of a forced migration experience. Second, the memories of Nazi forced labour have often been used to represent the experiences of collaboration and defeat in World War Two in the respective countries. Third, national political and moral economies have shaped the societal status of former forced labourers' memories. These memories have hardly found their proper place in most of the respective national pasts.